2019
DOI: 10.1186/s12888-019-2344-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self-stigma and its association with self-esteem among psychiatric patients in a Nepalese teaching hospital: a cross-sectional study

Abstract: BackgroundStigma against mental illness cuts across all age, religion, ethnic origin or socio-economic status. Similarly, self-stigma among psychiatric patients is also prevalent worldwide. The consequences of self-stigma are low self-esteem, increased severity of symptoms, low treatment adherence, increased rate of suicidality and decreased quality of life. Thus, this study aims to find the prevalence of self-stigma and its association with self-esteem of patients with mental illness in Nepal.MethodsThis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
41
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 37 publications
8
41
2
2
Order By: Relevance
“…The obtained results reveal the presence of IS in the whole sample, with slightly higher IS scores in Group-I, even though these differences were not statistically significant. These results are similar to other studies where the presence of moderate IS is also observed throughout the sample, but significant differences in IS scores were normally found in these studies, with more IS in people who had a diagnosis of SMI (Alonso et al, 2008;Holubova et al, 2018;Karidi et al, 2015;Maharjan & Panthee, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…The obtained results reveal the presence of IS in the whole sample, with slightly higher IS scores in Group-I, even though these differences were not statistically significant. These results are similar to other studies where the presence of moderate IS is also observed throughout the sample, but significant differences in IS scores were normally found in these studies, with more IS in people who had a diagnosis of SMI (Alonso et al, 2008;Holubova et al, 2018;Karidi et al, 2015;Maharjan & Panthee, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…It is characterized by cognitive, emotional, and behavioral components often conceptualized as internalized or enacted stigma affecting a particular trait, among individuals (10). Enacted stigma is the negative attitudes held by members of the public about devalued people whereas self-stigma occurs when people internalize those public attitudes and suffer numerous negative consequences as a result (11).…”
mentioning
confidence: 99%
“…Çalışmadaki katılımcıların ifade ettiği rollerini yerine getirememe ve sosyal yaşamdaki dışlanma bireylerde içselleştirilmiş damgalanmaya neden olabilir ki, yapılan çalışmalar içselleştirilmiş damgalanma ile düşük özsaygı arasındaki ilişkiyi ortaya koymaktadır [22,[33][34][35]…”
Section: 110başetmeunclassified